Research methods and statistics in psychology - Coolican, Hugh (Psychology Press, 2014)
"Research Methods and Statistics in Psychology, sixth edition, provides comprehensive coverage of both quantitative and qualitative methods and statistics. The new edition has been updated to reflect recent software updates and advances in knowledge. This classic research methods text is an essential purchase for all psychology students studying at degree level and beyond"--